2014
DOI: 10.1016/j.celrep.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The DGCR8 RNA-Binding Heme Domain Recognizes Primary MicroRNAs by Clamping the Hairpin

Abstract: SUMMARY Canonical primary microRNA transcripts (pri-miRNAs) are characterized by a ~30-bp hairpin flanked by single-stranded regions. These pri-miRNAs are recognized and cleaved by the Microprocessor complex consisting of the Drosha nuclease and its obligate RNA-binding partner DGCR8. It is not well understood how the Microprocessor specifically recognizes pri-miRNA substrates. Here we show that in addition to the well-known double-stranded RNA-binding domains, DGCR8 uses a dimeric heme-binding domain to direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 41 publications
7
93
2
Order By: Relevance
“…Although so far little is known on how the selectivity of ADAR1 binding to different pri-miRNAs is achieved, these observations are consistent with the notion that ADAR1 prefers to bind dsRNAs, but with little sequence specificity. Importantly, it was recently reported that two DGCR8 dimers clamp a pri-miRNA hairpin using their RNA-binding heme domain to activate DROSHA cleavage [52] (Figure 6C), thus the ADAR1 binding to pri-miRNA hairpin can compete with DGCR8 to inhibit pri-miRNA processing. Finally, as no A-to-I editing was identified in primary miR302s (data not shown), it further suggests that ADAR1 binding may not always lead to adenosine deamination; for instance, ADAR1 may bind to dsRNAs formed across introns and promote exon circularization [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although so far little is known on how the selectivity of ADAR1 binding to different pri-miRNAs is achieved, these observations are consistent with the notion that ADAR1 prefers to bind dsRNAs, but with little sequence specificity. Importantly, it was recently reported that two DGCR8 dimers clamp a pri-miRNA hairpin using their RNA-binding heme domain to activate DROSHA cleavage [52] (Figure 6C), thus the ADAR1 binding to pri-miRNA hairpin can compete with DGCR8 to inhibit pri-miRNA processing. Finally, as no A-to-I editing was identified in primary miR302s (data not shown), it further suggests that ADAR1 binding may not always lead to adenosine deamination; for instance, ADAR1 may bind to dsRNAs formed across introns and promote exon circularization [55].…”
Section: Discussionmentioning
confidence: 99%
“…The iCLIP clusters are depicted as purple rectangles. (C) Two DGCR8 dimers clamp a pri-miRNA hairpin and activate Drosha cleavage (middle) [52]. The binding of ADAR1 to hairpins of pri-miR302s competes with DGCR8 binding, resulting in an inhibitory effect on pri-miR302 processing (right).…”
Section: Catalytically Inactive Adar1-e912a Rescues Retarded Neural Imentioning
confidence: 99%
See 1 more Smart Citation
“…Drosha alone has no specific pri-miRNA cleavage activity, because it requires its partner DGCR8 for substrate recognition [6,7]. DGCR8 binds to key structural elements in pri-miRNAs; higher order structures of DGCR8 and Drosha appear to be required for Drosha-mediated cleavage [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Heme inhibits the interaction between P53 and its target DNA element and facilitates the nuclear export and proteasomal degradation of P53 [11]. Heme is also required for the proper binding of the microprocessor subunit DGCR8 to primary microRNA transcripts (pri-miRNAs), and thus plays a critical role in the processing of pri-miRNAs [12][13][14].…”
mentioning
confidence: 99%